Characterization of Japanese Plum (Prunus salicina) PsMYB10 Alleles Reveals Structural Variation and Polymorphisms Correlating With Fruit Skin Color - Fiol, Arnau; García-Gómez, Beatriz E.; Jurado-Ruiz, Federico; Alexiou, Konstantinos; Howad, Werner; Aranzana, Maria José (Frontiers in Plant Science, 2021)
The red to blue hue of plant organs is due to anthocyanins, water-soluble flavonoid pigments. The accumulation of these pigments is regulated by a complex of R2R3-MYB transcription factors (TF), basic-helix-loop-helix (bHLH) and WD-Repeat (WDR) proteins (MBW complex). In Rosaceae species, R2R3-MYBs, in particular MYB10 genes, are responsible for part of the natural variation in anthocyanin colors. Japanese plum cultivars, which are hybrids of Prunus salicina, have high variability in color hue and pattern, going from yellow-green to red and purple-blue, probably as a result of the interspecific hybridization origin of the crop. Because of such variability, Japanese plum can be considered an excellent model to study color determination in Rosaceae fruit tree species. Here we cloned and characterized alleles of PsMYB10 genes in the linkage group LG3 region, where QTLs for organ color have been mapped in other Prunus species. Allele segregation in bi-parental populations as well as in a panel of varieties, combined with the whole genome sequence of two varieties with contrasting fruit color, allowed the organization of the MYB10 alleles into haplotypes. With this strategy, alleles were assigned to genes and at least three copies of PsMYB10.1 were identified in some varieties. In total we observed six haplotypes which were able to characterize 91.36% of the cultivars. In addition, two alleles of PsMYB10.1 were found to be highly associated with anthocyanin and anthocyanin-less skin. Their expression during fruit development confirm their role in fruit skin coloration. Here we provide a highly efficient molecular marker for early selection of colored or non-colored fruits in Japanese plum breeding programs.